CERTAIN RELATIONS BETWEEN MOTORCYCLE TESTS FOR ASSESSMENT OF COORDINATION AND EXPLOSIVE POWER WITH THE MEASURES OF THE SUCCESSFUL PERFOMANCE OF THE GYMNASTIC ELEMENT UPRISE FORWARD TO SUPPORT L-SIT ON RINGS - Spasovska, Katerina; Vuksanovikj, Vladimir (Faculty of Physical Education, Sports and Health, Sc.Cyril and Methodius University,Skopje, Macedonia, 2023)
For achieving the objectives of this research, a research procedure was conducted on a sample of 68 respondents, male students from the first year at the age of 18 years +/- 6 m. at the Faculty of Physical Education, Sports and Health in Skopje, Republic of Macedonia. A total of 20 manifest motor variables were applied to the selected sample of respondents, of which twelve (12) for assessment of coordination (coordination of whole body, coordination of legs, coordination of rapid complex movements and reorganization of dynamic stereotype), as well as eight (8) explosive power assessment tests (type of jumps and type of ejection). The evaluation of the technical performance of the gymnastic element uprise forward to support L-sit of the gymnastic equipment rings was performed by 4 qualified judges who are well acquainted with the subject of evaluation. A regression analysis was used to determine the relationships between motor tests to assess coordination of separate body parts and the explosive strength type of jumps and ejection. In the regression analyzes, the tests of coordination and explosive strength were used as a predictor, and the gymnastic element uprise forward to support L-sit of the circles was taken as a criterion. The predictors showed a statistically significant impact on the criterion.
Keywords: gymnastics; coordination; explosive strength; Regression Analysis